Charting Churches in a Changing Europe: Charta Oecumenica and the Process of Ecumenical Encounter - Noble, Tim (Currents of Encounter - Studies on the Contact between Christianity and Other Religions, Beliefs, an, 2006)
The countries of Europe are seeking to redefine themselves, both individually and in relation to each other. This volume examines the role of the Christian churches at various levels of that process. The Charta Oecumenica , a ground-breaking document from the Conference of Churches in Europe and the Council of European Bishops' Conferences, aimed to set forth the ecumenical response of the European Christian Churches to the living out of faith in today's world. Four theologians, Protestant, Roman Catholic, Orthodox and Lutheran, respond to this document, assessing its strengths and the areas where further development is required. At least implicitly this discussion raises questions about the nature of catholicity and communion, a topic the following four essays address. What is catholicity, what happens when there is too strong an emphasis on the national church, and are there models of gradual church communion to which the churches could assent? Gradual communion sets out to attain full, including sacramental, unity and the final two essays explore how sacramental theology might assist in this process.